The Relationship Between Maternal Self-Efficacy and Feeding Patterns and the Incidence of Wasting among Children Under Five at the Penfui Community Health Center - Margarince Katupu; Astuti Nur; Asweros Umbu Zogara (Media Publikasi Cendekia Indonesia, 2026)
Wasting remains a serious public health problem in Indonesia, particularly in East Nusa Tenggara Province. Maternal factors, such as self-efficacy (confidence in one’s own abilities) and feeding practices, are believed to play a crucial role in determining young children's nutritional status. This study aimed to analyze the relationships among maternal self-efficacy, feeding patterns, and the incidence of wasting among children under five in the working area of the Penfui Community Health Center. An observational analytic study with a cross-sectional design was conducted. A total of 56 children were selected using simple random sampling. Maternal self-efficacy and feeding patterns were assessed using structured questionnaires, and wasting status was determined from anthropometric measurements using the weight-for-height index (WH). Data were analyzed using the chi-square test with a significance level of p < 0.05. The results showed a statistically significant association between maternal self-efficacy and the incidence of wasting (p < 0.05). The association between feeding patterns and wasting could not be statistically analyzed because the sample was entirely homogenous, with all respondents reporting appropriate feeding practices. In conclusion, maternal self-efficacy is an important factor associated with wasting among children under five. Therefore, nutrition interventions should emphasize strengthening maternal capacity and confidence in implementing appropriate child-feeding behaviors.